The role of endoscopic ultrasound in a case of lung cancer with jaundice - Castro-Pocas, FM (2018)
Lung cancer is one of the major causes of death in the world. Small cell carcinoma is the most aggressive type and can spread rapidly. The association of a small cell carcinoma with hepatic hilar metastasis and biliary obstruction is rare. Endoscopic ultrasound allows the aspiration of a cytology sample from adenopathies for diagnostic purpose. We present the case of a patient with lung cancer, with lymph node metastasis to the hepatic hilum and extrinsic biliary tree compression. Endoscopic ultrasound allowed the definitive diagnosis of hepatic hilar metastasis of a lung small cell carcinoma. To the author's knowledge it was the first time that endoscopic ultrasound was used for the diagnosis of hepatic hilar lymph node metastasis of lung cancer.